Food availability in rural Kansas: coping strategies for people living in low access food areas - Rissler, Patrick S. (Kansas State University, 2015)
In the last 70 years, there has been a decline in population of rural Kansas. For example Gove, KS, the county seat of Gove County has seen a population decline of 355% from 284 in 1940 to 80 residents in the 2010 US Census (US Census). Along with general population decline in rural areas, is decline the overall number of farms, while the average farm size has increased (Kansas Dept. of Agriculture). The decline of the population of rural communities has caused the erosion of basic infrastructure, leaving many communities lacking access to basic services. One of the crucial components of the rural infrastructure is the rural grocery store. Since 2007, in Kansas communities with populations under 2,500 people, 82 grocery stores have closed. On average, rural Kansans now drive over 10 miles each direction to obtain their groceries. Proctor (2013) describes how the loss of a grocery store can affect a community: “Rural grocery stores are part of the economic engine that sustains rural communities," “they are a significant source of local taxes, powering the creation and maintenance of civic services and amenities. They provide essential, stable jobs – butchers, cashiers, managers, and stockers – at a time when we are desperate for employment opportunities.” The objectives of this study are to describe the food desert conditions of three rural communities in Kansas, to understand the trends regarding rural grocery stores, and to better understand the issues of access to healthy foods faced by people living in these areas.
Keywords: Food Deserts; Copping Strategies; Rural Kansas; Sociology (0626)